2009
DOI: 10.1016/j.jcs.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Wholemeal wheat bread: A comparison of different breadmaking processes and fungal phytase addition

Abstract: 14The effect of different breadmaking processes (conventional, frozen dough, frozen 15 partially baked bread) and the effect of the storage periodon the technological quality of 16 the fresh wholemeal wheat breads are investigated. In addition, the impact of the 17 exogenous fungal phytase on the phytate content was also determined. Results showed 18 that breadmaking technology significantly affected the quality parameters of wholemeal 19 breads (specific volume, moisture content, crumb and crust colour, crumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 30 publications
3
32
0
2
Order By: Relevance
“…The bread volume is related to the quantity and quality of gluten (Chloupek et al 2008;Rosell et al 2009). Bread volume is measured as one of the most important criteria in evaluating bread quality (Yamsaengsung et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The bread volume is related to the quantity and quality of gluten (Chloupek et al 2008;Rosell et al 2009). Bread volume is measured as one of the most important criteria in evaluating bread quality (Yamsaengsung et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Technology of baking also affects the quality of wholemeal breads. Rosell et al [2009] reported that wholemeal bread prepared by bake-off technology was softer and its hardness was not infl uenced by storage conditions. It has been also reported that addition of sourdough and dietary fi ber (inulin and oat fi bers) affects the nutritional value of wheat breads prepared by bake-off technology [Kopeć et al 2011].…”
Section: An Addition Of Sourdough and Whey Proteins Affects The Nutrimentioning
confidence: 99%
“…Phyta ses, phosphohydrolases of myo-inositol hexakisphosphate, hydrolyse phytate to a pool of lower myo-inositol phosphates (3,4). In breadmaking, phosphorolytic activity originates from wheat or rye fl our enzymes as well as from the yeast phytase (5)(6)(7). The joint action of these enzymes determines the fi nal profi le of inositol phosphates and may also lead to the formation of free myo-inositol (8).…”
Section: Introductionmentioning
confidence: 99%
“…The strategy presented here is based on the concept of enzymatic conversion of endogenous phytates of rye fl our into myo-inositol by means of commerci al microbial phytases added to the dough. Although phytase application in the breadmaking has been studied by a few researchers (5)(6)(7)21), there is no evidence to suggest that this can be utilized as a method for producing bread with enhanced myo-inositol content.…”
Section: Introductionmentioning
confidence: 99%